Biblioteca - Encalada Rodríguez, Estefany Carolina (2018)
The urban parish of La Mariscal belongs to the province of Pichincha in the Sierra region of Ecuador. This sector is known nationally as a socio-cultural point in which certain economic activities are developed. It is characterized for containing several buildings of patrimonial character which gives a historical value to the study area. The workshop ARO-960 (2017-2) elaborates a plan of Territorial Organization, that allows to understand the dynamics, complexity, possible conflicts and solutions that are reflected in the vision to future. The proposal seeks to revalue the cultural and historical character of the city, therefore equipment is proposed that responds to the formal, functional and symbolic needs of the users. The Library originates from the vision to the future, mainly as a milestone of the city, that allows strengthening the local culture of the Marshal. The degree work focuses on providing computer media and generating entertainment and leisure activities. In order to ensure the welfare of the community, through access to various knowledge, ideas and opinions.